2008
DOI: 10.1016/j.cbpb.2008.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic stress-induced increase in the expression of glutamate-cysteine ligase and glutathione levels in the symbiotic sea anemone Aiptasia pallida

Abstract: Hyperthermic stress is known to trigger the loss of unicellular algae from a number of symbiotic cnidarians, a phenomenon commonly referred to as bleaching. Oxidative and nitrosative stress have been suggested to play a major role during the process of bleaching, however the underlying molecular mechanisms are still poorly understood. In animals, the intracellular tripeptide glutathione (GSH) is involved in antioxidant defense, redox homeostasis and intracellular redox signaling. Therefore, we tested the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…In addition, pools of the antioxidant compound glutathione were elevated in both partners. Glutathione is a tripeptide antioxidant that serves as an important electron donor during oxidative stress in Symbiodinium (Lesser, 2006;Krueger et al, 2014) and in the cnidarian host (Downs et al, 2002;Desalvo et al, 2008;Sunagawa et al, 2008), consistent with the findings of the present study.…”
Section: Organic Acids Intermediates and Antioxidantssupporting
confidence: 92%
“…In addition, pools of the antioxidant compound glutathione were elevated in both partners. Glutathione is a tripeptide antioxidant that serves as an important electron donor during oxidative stress in Symbiodinium (Lesser, 2006;Krueger et al, 2014) and in the cnidarian host (Downs et al, 2002;Desalvo et al, 2008;Sunagawa et al, 2008), consistent with the findings of the present study.…”
Section: Organic Acids Intermediates and Antioxidantssupporting
confidence: 92%
“…S-adenosylmethionine plays a critical role in the synthesis of glutathione (GSH), one of the most important antioxidants, through its transsulfation pathway (Droge, 2002). Sunagawa et al (2008) suggested that GSH levels in the sea anemone increased 1.5-fold in response to thermal stress. Methionine metabolism in corals may likewise be affected by heat stress.…”
Section: High Temperaturementioning
confidence: 99%
“…Apoptotic elements are similarly induced by hyperthermal stress in the host tissues of the symbiotic sea anemones Anemonia virdis (32), Aiptasia pallida (33,34), and Anthopelura elegantissima (35). Elements of the NF-B signaling pathway of apoptosis in cnidarians are highly conserved traits (36), including genes of the caspase cascade and the pro-apoptotic and antiapoptotic B-cell lymphoma 2 (Bcl-2) family of proteins (33,29) that likely predate the evolution of animal multicellularity via endosymbiotic incorporation of aerobic bacteria as the ancestral proto-mitochondria of unicellular eukaryotes (37).…”
mentioning
confidence: 99%